Preparation method and application of porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects
By preparing porous composite materials rich in carbon and cobalt -like disinfection, the problem of poor lithium sulfur battery, slow shuttle effect and dynamic dynamics of lithium sulfur batteries, and realized lithium sulfur batteries with efficient electrochemical properties and long life.
Patent Information
- Application Number
- CN202411264336.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Lithium sulfur batteries have problems such as poor conductivity, shuttle effect, severe volume expansion and slow kinetics in electrochemical reactions, resulting in poor rate performance, fast capacity drop and low life.
Using porous composite materials rich in carbon and cobalt -like deficiency, prepare through steps such as ultrasonic reaction, scorched ear heat treatment, and acetate solution treatment to improve the electrical, compared with the surface area and pores of the material, thereby suppress the shuttle effect and accelerate liquid solid conversion dynamics dynamic dynamics Essence
Significantly improve the conductivity and cycle stability of lithium-sulfur batteries, enhance high-rate capacity and reversibility, extend battery life and reduce energy consumption.
Smart Images

Figure CN118825244B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects, belonging to the technical field of lithium-sulfur battery cathode materials. Background Art
[0002] Lithium-sulfur batteries have advantages such as high theoretical energy density (2600 Wh / kg) and low cost, and are one of the most promising next-generation new battery systems. However, their commercial progress is still restricted in the following aspects: (1) In the electrochemical reaction, the electron insulation of S and Li2S will also cause slow reaction kinetics and serious polarization, resulting in poor rate performance of lithium-sulfur batteries; (2) The intermediate soluble polysulfide (Li2S n , 2 < n ≤ 8) generates a shuttle effect under the drive of the concentration gradient, resulting in rapid decline of the battery capacity and low life; (3) The volume expansion of the active material during charge and discharge will cause a sharp attenuation of the battery capacity and the failure of the battery; (4) The liquid-solid conversion, as the rate-determining step of the reaction kinetics, needs to overcome a large reaction energy barrier, resulting in slow kinetics under practical conditions.
[0003] In the prior art, the above problems are mainly solved by developing conductive carbon-based materials or polar catalysts. However, although the single use of carbon materials can solve the problem of poor conductivity and alleviate the volume expansion, the interaction between the non-polar surface of the conductive carbon material and the polar polysulfide ions is weak, and the soluble polysulfide cannot be effectively anchored, resulting in a large amount of polysulfide shuttling to the negative electrode through the separator, thus greatly reducing the effective utilization rate of elemental sulfur. The polar material as a catalyst can effectively solve the shuttle effect of polysulfide, but the low conductivity of this kind of material will seriously hinder the ion / electron transfer rate. Therefore, constructing a composite material of conductive carbon and polar catalyst is an effective strategy to simultaneously solve the problems of poor conductivity, shuttle effect, serious volume expansion and slow kinetics of lithium-sulfur batteries in the prior art. At present, most of these materials are obtained through cumbersome preparation processes, which are often time-consuming and energy-consuming, and the preparation efficiency is very low. In addition, most of the research work only composes the conductive carbon and the polar catalyst, without effectively regulating the two components, and further improving their electrochemical performance.
[0004] The Chinese invention patent document with publication number CN110600690A discloses a zeolite imidazole framework-derived nitrogen-doped hierarchical porous carbon @ manganese tetraoxide @ carbon / sulfur (N-HPC@Mn3O4@NC / S) and its preparation method and application. The patent prepares N-HPC separately through a complicated preparation process, then grows Mn3O4 on the surface of N-HPC through a hydrothermal reaction, and finally wraps a layer of NC through a polymerization reaction and calcination process to prepare a N-HPC@Mn3O4@NC composite material and apply it to lithium-sulfur batteries. This patent mainly takes advantage of the inherent advantages of carbon materials and oxides without modifying these materials themselves, thereby further optimizing their performance. In addition, the preparation method is relatively long and has high energy consumption. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects, which can solve the problems of poor conductivity, shuttle effect, severe volume expansion and slow kinetics of lithium-sulfur batteries in the prior art. The material exhibits the characteristics of high efficiency and high conductivity, significant buffering effect, fast lithium ion diffusion kinetics and strong chemical adsorption of lithium polysulfide, and shows stable cycle life and high rate performance in the application of lithium-sulfur battery positive electrode materials, and has broad industrial prospects.
[0006] To achieve this object, the technical solution of the present invention is:
[0007] A method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects comprises the following steps:
[0008] (1) adding cobalt nitrate, sodium chloride and nano-calcium carbonate into methanol, and ultrasonicating for 0.5-1h to obtain a first mixed solution; dissolving 2-methylimidazole into methanol to obtain a second mixed solution;
[0009] (2) After the first mixed solution and the second mixed solution are uniformly mixed, ultrasonic reaction is carried out at room temperature for 4-8 hours, and then centrifugation, washing, and vacuum drying are performed to obtain a first precursor;
[0010] (3) Grinding the first precursor into a powder of 200-300 mesh, and then placing sulfur powder and the first precursor powder on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively, and then performing Joule heat treatment under a nitrogen protective atmosphere to obtain a second precursor;
[0011] (4) Adding the second precursor to an aqueous acetic acid solution, reacting at 30-50° C. for 1-3 hours, centrifuging, washing, and vacuum drying to obtain a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects.
[0012] Furthermore, in step (1), the particle size of the nano calcium carbonate is 20-50 nm.
[0013] Furthermore, in the step (1), the ratio of cobalt nitrate, sodium chloride, nano-calcium carbonate and methanol in the first mixed solution is: 1mmol:1.2-2mmol:2-4mmol:50mL; the ratio of 2-methylimidazole and methanol in the second mixed solution is: 4-8mmol:50mL.
[0014] Furthermore, in step (2), the washing conditions are: washing with methanol three to five times; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 18-24 h.
[0015] Furthermore, in the step (3), the ratio of the amount of sulfur powder to the first precursor powder is 0.2-1g:0.1g.
[0016] Furthermore, in step (3), the conditions of the Joule heat treatment are: heat treatment temperature 500-1500°C, heating rate 2000-3000°C / s, and Joule heat treatment times 4-10 times. The Joule heat treatment is heating from room temperature to the target temperature and then naturally cooling to room temperature, which is represented as one time.
[0017] Furthermore, in step (4), the concentration of the acetic acid aqueous solution is 50-70% by mass of acetic acid; and the dosage ratio of the second precursor to the acetic acid aqueous solution is 0.1-0.3 g:10 ml.
[0018] Furthermore, in step (4), the washing conditions are: washing with deionized water for three to five times; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 18-24 h.
[0019] Another object of the present invention is to provide an application of a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects prepared by the above method, which is applied to the positive electrode of a lithium-sulfur battery.
[0020] The beneficial effects of the present invention are:
[0021] (1) Compared with the traditional calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high preparation efficiency and low energy consumption, which helps to inhibit the shrinkage (collapse) of the pore structure at high temperature. At the same time, the extreme environment caused by rapid temperature rise gives the material a large number of defects, while extremely rapid cooling can retain these defects to a large extent.
[0022] (2) The present invention grinds the first precursor into 200-300 mesh powder, which helps to reduce the Joule heat treatment and subsequent modification treatment conditions and improve the performance of the material. In addition, it can also prevent local overheating during the calcination process from causing the collapse of the pores and the agglomeration of metal atoms.
[0023] (3) The preparation method of the present invention is simple. By introducing nano calcium carbonate and sodium chloride as pyrolysis aids, the two have a synergistic effect, which is beneficial to increase the conductivity, specific surface area, carbon defect density, and defect amount of CoS of carbon materials; post-treatment with acetic acid aqueous solution not only helps to remove excess calcium carbonate, but also helps to form mesopores and macropores, and has a good pore-forming effect when used in conjunction with Joule heat treatment technology. The porous structure and high specific surface area are beneficial to alleviate the volume expansion during the charge and discharge process, increase the dispersion of CoS, and then increase the number of active sites of CoS. Carbon defects can significantly improve the conductivity of the material, while the defects inside CoS can significantly improve its polysulfide anchoring and catalytic conversion performance, thereby inhibiting the shuttle effect and accelerating the kinetics of liquid-solid conversion.
[0024] (4) The porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects prepared by the present invention has a specific surface area and pore size range of 970.8-1000.2 m 2 / g, 5-65nm, and outstanding performance in the positive electrode of lithium-sulfur batteries. Especially at a high rate of 1C, the initial specific capacity of the lithium-sulfur battery is as high as 700.5-784.6mAh / g, and after 400 cycles, the capacity retention rate is 80.3-83.8%; at a high rate of 4C, the initial specific capacity is as high as 620.5-681.8mAh / g; the recovery rate when switching from 4C to 0.1C is 90.4-91.2%, indicating good high-rate capacity and reversibility. This material significantly improves the cycle life and rate performance of lithium-sulfur batteries and the specific capacity of batteries by enhancing the intrinsic advantages of carbon materials and CoS and then exerting their synergistic effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The Raman spectra of the porous lithium-sulfur battery composite materials rich in carbon and cobalt sulfide defects of Example 1 and Comparative Examples 1-2;
[0026] Figure 2 This is a high-resolution transmission electron microscopy image of the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects of Example 1;
[0027] Figure 3 This is a graph showing the electrochemical cycling performance of the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects of Example 1 at a 1C rate;
[0028] Figure 4 The cycling curves at different rates of the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects of Example 1. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.
[0030] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.
[0031] In a specific embodiment of the present invention, the Joule heat rapid heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1
[0032] (1) Add 1 mmol of cobalt nitrate, 1.5 mmol of sodium chloride, and 3 mmol of nano-calcium carbonate with a particle size of 20 nm into 50 mL of methanol, and ultrasonicate for 0.8 h to obtain a first mixed solution; add 6 mmol of 2-methylimidazole into 50 mL of methanol, and ultrasonicate for 8 min to obtain a second mixed solution;
[0033] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 6 hours, centrifugation, methanol washing four times, and vacuum drying at 70° C. for 22 hours to obtain a first precursor;
[0034] (3) Grind the first precursor into powder, sieve out 300-mesh powder through a 300-mesh sieve, and then place 1.5 g of sulfur powder and 0.3 g of the first precursor powder on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, perform Joule heat treatment 6 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 850°C and a Joule heat treatment heating rate of 2500°C / s, to obtain a second precursor;
[0035] (4) 0.2 g of the second precursor was added to 10 mL of a 60% acetic acid aqueous solution, reacted at 45 °C for 2 h, centrifuged, washed four times with deionized water, and vacuum dried at 70 °C for 22 h to obtain a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects. Example 2
[0036] (1) Add 1 mmol of cobalt nitrate, 1.2 mmol of sodium chloride, and 2 mmol of nano-calcium carbonate with a particle size of 50 nm to 50 mL of methanol, and ultrasonicate for 0.5 h to obtain a first mixed solution; add 4 mmol of 2-methylimidazole to 50 mL of methanol, and ultrasonicate for 5 min to obtain a second mixed solution;
[0037] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 4 hours, centrifugation, methanol washing three times, and vacuum drying at 50° C. for 24 hours to obtain a first precursor;
[0038] (3) Grind the first precursor into powder, sieve out 200-mesh powder through a 200-mesh sieve, and then place 0.4 g of sulfur powder and 0.2 g of the first precursor powder on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, perform Joule heat treatment 10 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 500°C and a Joule heat treatment heating rate of 2000°C / s, to obtain a second precursor;
[0039] (4) 0.1 g of the second precursor was added to 10 mL of a 50% acetic acid aqueous solution, reacted at 30 °C for 3 h, centrifuged, washed three times with deionized water, and vacuum dried at 50 °C for 24 h to obtain a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects.
[0040] Example 3
[0041] (1) Add 1 mmol of cobalt nitrate, 2 mmol of sodium chloride, and 4 mmol of nano-calcium carbonate with a particle size of 40 nm into 50 mL of methanol, and ultrasonicate for 1 hour to obtain a first mixed solution; add 8 mmol of 2-methylimidazole into 50 mL of methanol, and ultrasonicate for 10 minutes to obtain a second mixed solution;
[0042] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 8 hours, centrifugation, methanol washing five times, and vacuum drying at 80° C. for 18 hours to obtain a first precursor;
[0043] (3) Grind the first precursor into powder, sieve out 300-mesh powder through a 300-mesh sieve, and then place 4 g of sulfur powder and 0.4 g of the first precursor powder on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, perform Joule heat treatment 4 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 1500°C and a Joule heat treatment heating rate of 3000°C / s, to obtain a second precursor;
[0044] (4) 0.3 g of the second precursor was added to 10 mL of a 70% acetic acid aqueous solution, reacted at 50 °C for 1 h, centrifuged, washed with deionized water five times, and vacuum dried at 80 °C for 18 h to obtain a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects.
[0045] Example 4
[0046] (1) Add 1 mmol of cobalt nitrate, 1.4 mmol of sodium chloride, and 2.5 mmol of nano-calcium carbonate with a particle size of 35 nm to 50 mL of methanol, and ultrasonicate for 0.8 h to obtain a first mixed solution; add 5 mmol of 2-methylimidazole to 50 mL of methanol, and ultrasonicate for 8 min to obtain a second mixed solution;
[0047] (2) After the first mixed solution and the second mixed solution are evenly mixed, ultrasonic reaction is carried out at room temperature for 7 hours, centrifugation, methanol washing four times, and vacuum drying at 60° C. for 24 hours to obtain a first precursor;
[0048] (3) Grind the first precursor into powder, sieve out 250-mesh powder through a 250-mesh sieve, and then place 0.8 g of sulfur powder and 0.2 g of the first precursor powder on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, perform Joule heat treatment 8 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 1000°C and a Joule heat treatment heating rate of 2800°C / s, to obtain a second precursor;
[0049] (4) 0.15 g of the second precursor was added to 10 mL of 65% acetic acid aqueous solution, reacted at 45 °C for 3 h, centrifuged, washed four times with deionized water, and vacuum dried at 60 °C for 24 h to obtain a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects. Comparative Example 1
[0050] The difference between Comparative Example 1 and Example 1 is that the heating device in step (3) is different, the Joule heat rapid heating device is replaced with a high-temperature tube furnace, and the other steps remain unchanged. The specific operation is as follows:
[0051] The first precursor was ground into powder, and 300-mesh powder was screened out through a 300-mesh sieve. Then, 0.1 g of the first precursor powder was placed in the center of the temperature zone of a high-temperature tube furnace, and 0.5 g of sulfur powder was placed upstream of the gas. The mixture was calcined in a nitrogen atmosphere at a temperature of 850°C and a heating rate of 5°C / min. The reaction was kept warm for 2 hours to obtain a second precursor. Comparative Example 2
[0052] The difference between Comparative Example 2 and Example 1 is that no sodium chloride and nano-calcium carbonate are added in step (1), and the other steps remain unchanged. Comparative Example 3
[0053] The difference between Comparative Example 3 and Example 1 is that no sodium chloride is added in step (1), and the other steps remain unchanged. Comparative Example 4
[0054] The difference between Comparative Example 4 and Example 1 is that no nano calcium carbonate is added in step (1), and the other steps remain unchanged. Comparative Example 5
[0055] The difference between Comparative Example 5 and Example 1 is that there is no acetic acid aqueous solution treatment in step (4), and the other steps remain unchanged. Comparative Example 6
[0056] The difference between Comparative Example 6 and Example 1 is that there is no grinding process in step (3), and the other steps remain unchanged. Comparative Example 7
[0057] The difference between Comparative Example 7 and Example 1 is that the particle size of the nano-calcium carbonate in step (1) is different, and the other parameters remain unchanged. The nano-calcium carbonate with a particle size of 20 nm is replaced with nano-calcium carbonate with a particle size of 100 nm.
[0058] Application Example 1
[0059] The porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects was used as the positive electrode, lithium foil as the negative electrode, polypropylene porous membrane (Celgard2300) as the separator, and the electrolyte (a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) was assembled in a glove box full of inert atmosphere protection. The battery was tested for electrochemical cycle performance at 1C rate and high rate test at 0.1-4C on the CT-4008-5A6V system. The test results are shown in Table 1.
[0060] The porous lithium-sulfur battery composite materials rich in carbon and cobalt sulfide defects obtained in Examples 1-4 and Comparative Examples 1-7 were subjected to a nitrogen full adsorption test (N2-BET). The test results are shown in Table 1, wherein the N2-BET test includes a specific surface area test and a pore size distribution (NLDFT model full pore distribution) test.
[0061]
[0062] From the comparison of Examples 1-4 and Comparative Example 1 in Table 1, it can be seen that both tubular furnace calcination and Joule heat rapid heating device will affect the specific surface area and pore size of the material, but the Joule heat rapid heating device has a greater impact on the specific surface area and defects (carbon defects and cobalt sulfide defects) and pore size of the material, and the performance (capacity, cycle) of the material after treatment by the Joule heat rapid heating device is more superior. From the comparison of Examples 1-6 and Comparative Example 2, it can be seen that sodium chloride and calcium carbonate help to improve the pore size distribution and specific surface area of the material, thereby affecting the performance (capacity, cycle) of the material. From the comparison of Example 1 with Comparative Example 2 and Comparative Example 3, it can be seen that sodium chloride affects the conductivity, pore size, specific surface area, defects (caused by Figure 1 and Figure 2 By comparing Example 1 with Comparative Example 2 and Comparative Example 4, it can be seen that the pore size, specific surface area, and defects (caused by Figure 1 and Figure 2 Therefore, the addition of sodium chloride and nano calcium carbonate has a synergistic effect, and then synergistically affects the performance of the lithium-sulfur battery through defects, specific surface area, pore size, and conductivity. From the comparison between Example 1 and Comparative Example 5, it can be seen that the acetic acid aqueous solution can remove excess calcium carbonate and also form pores, mainly by affecting the pore size of the material and thus affecting the performance of the material (capacity, cycle). From the comparison between Example 1 and Comparative Example 6, it can be seen that under the same treatment conditions, the mesh number of the powder will also affect the pore size distribution and specific surface area, and thus affect the performance of the material (capacity, circulation, and good high rate performance). This is mainly because the larger the mesh number of the powder, the more conducive it is to the treatment of the acetic acid aqueous solution and the calcination process. First, it can improve the treatment efficiency of the acetic acid aqueous solution, and second, it can prevent the material from being locally overheated during calcination, thereby causing the pore collapse of the material and the agglomeration of metal atoms. From Example 1 and Comparative Example 7, it can be seen that when the particle size of the nano-calcium carbonate is larger, the performance (capacity, circulation) of the material is limited. This may be because the larger the particle size of the nano-calcium carbonate, the nano-calcium carbonate is only mixed with the material, and does not enter the interior of the material during the in-situ synthesis of the first precursor, resulting in poor performance of the material after calcination and acid treatment.
[0063] Figure 1 The Raman spectra of the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects of Example 1 and Comparative Examples 1-2 are shown in FIG. D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, it can be seen from the figure that I D / I GThe order of values is Example 1 (0.91) > Comparative Example 1 (0.78) and Comparative Example 2 (0.65). This indicates that Example 1 has a relatively high carbon defect, which is mainly caused by the pyrolysis aid sodium chloride and nano calcium carbonate powder and the rapid heating and cooling, in which the pyrolysis aid contributes more to the formation of defects than the Joule heat rapid heating device.
[0064] Figure 2 This is a high-resolution transmission electron microscopy image of a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects in Example 1. As can be seen from the figure, there are a large number of defects in the white circle part, indicating that the defect-rich CoS in Example 1.
[0065] Figure 3 This is the electrochemical cycle performance diagram of the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects of Example 1 at 1C rate. The battery showed a first-cycle discharge of 784.6 mAh / g. After 400 cycles, the capacity remained at 657.9 mAh / g, and the average capacity decay rate per cycle was 0.04%. Combined with the data in Table 1, compared with Example 1, Comparative Example 1 and Comparative Example 2 showed poor cycle stability and higher capacity decay rate under the same conditions. The main reasons for this performance advantage are as follows: the use of pyrolysis aids sodium chloride and sodium carbonate and rapid temperature rise and fall technology is conducive to increasing the specific surface area and defect content of the carbon base material and enriching the crystal defects of CoS, so that the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects has excellent sulfur loading capacity and conductivity, and the defects inside CoS can significantly improve its polysulfide anchoring and catalytic conversion performance, thereby inhibiting the shuttle effect and accelerating the kinetics of liquid-solid conversion, thereby showing excellent lithium-sulfur battery performance.
[0066] Figure 4 In the different rate performance diagrams of the porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects of Example 1, Example 1 can achieve a specific capacity of 681.8 mAh / g at a high charge and discharge rate of 4C, indicating that Example 1 has good rate performance. At the same time, at 0.1C and 4C current densities, the capacity reached 1144.5 mAh / g and 681.8 mAh / g, respectively, and then the capacity recovered to 1034.8 mAh / g after switching to 0.1C at 4C current density, and the capacity recovery rate reached 90.4%, indicating that the material has highly reversible electrochemical properties.
[0067] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects, characterized in that: The following steps are involved: (1) adding cobalt nitrate, sodium chloride and nano-calcium carbonate into methanol, and ultrasonicating for 0.5-1h to obtain a first mixed solution; dissolving 2-methylimidazole into methanol to obtain a second mixed solution; (2) After the first mixed solution and the second mixed solution are uniformly mixed, ultrasonic reaction is carried out at room temperature for 4-8 hours, and then centrifugation, washing, and vacuum drying are performed to obtain a first precursor; (3) Grinding the first precursor into a powder of 200-300 mesh, and then placing sulfur powder and the first precursor powder on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively, and then performing Joule heat treatment under a nitrogen protective atmosphere to obtain a second precursor; (4) adding the second precursor to an acetic acid aqueous solution, reacting at 30-50° C. for 1-3 hours, centrifuging, washing, and vacuum drying to obtain a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects; In the step (3), the conditions of the Joule heat treatment are: heat treatment temperature of 500-1500°C, heating rate of 2000-3000°C / s, and Joule heat treatment times of 4-10 times.
2. The method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 20-50 nm.
3. The method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects according to claim 1, characterized in that: In the step (1), the ratio of cobalt nitrate, sodium chloride, nano-calcium carbonate and methanol in the first mixed solution is: 1mmol:1.2-2mmol:2-4mmol:50mL; the ratio of 2-methylimidazole and methanol in the second mixed solution is: 4-8mmol:50mL.
4. The method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects according to claim 1, characterized in that: In the step (2), the washing conditions are: washing with methanol three to five times; and the vacuum drying conditions are: drying temperature 50-80°C, and drying time 18-24h.
5. The method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects according to claim 1, characterized in that: In the step (3), the ratio of the amount of sulfur powder to the first precursor powder is 0.2-1g:0.1g.
6. The method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects according to claim 1, characterized in that: In the step (4), the concentration of the acetic acid aqueous solution is 50-70% by mass of acetic acid; the dosage ratio of the second precursor to the acetic acid aqueous solution is 0.1-0.3 g:10 ml.
7. The method for preparing a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects according to claim 1, characterized in that: In the step (4), the washing conditions are: washing with deionized water three to five times; the vacuum drying conditions are: drying temperature 50-80°C, drying time 18-24h.
8. An application of a porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Apply it to the positive electrode of lithium-sulfur batteries.
Citation Information
Patent Citations
Zeolite-imidazole-framework derived nitrogen-doped hierarchical porous carbon@trimanganese tetroxide@carbon / sulfur and preparation method and application thereof
CN110600690A
Method for rapid Joule thermal synthesis of metal oxide-based material and application
CN116654972A
Materials and methods of use thereof
WO2024076558A1